Pengaruh Pengetahuan Perpajakan, Motivasi, dan Etika Profesi Perpajakan Terhadap Pemilihan Karir di Bidang Perpajakan (Studi Empiris pada Mahasiswa Akuntansi Universitas Islam Malang, dan Universitas Islam Negeri Maulana Malik Ibrahim Malang) - Rokhim, Mukhammad; Mahsuni, Abdul Wahid; Junaidi, Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2024)
This research was conducted to determine and analyze the influence of tax knowledge, motivation and professional ethics on choosing a career in taxation. The population in the study were students from the Faculty of Economics and Business, Accounting Study Program, Islamic University of Malang, and the Maulana Malik Ibrahim State Islamic University class of 2019 and 2020, the exact number of which is not known. The approach method uses a non-probability sampling technique, namely purposive sampling, which is a sample collection technique based on certain criteria using a questionnaire distributed to 75 respondents and using the SPSS analysis tool. The results of the research show that tax knowledge, motivation and professional ethics simultaneously influence the choice of a career in taxation and partially tax knowledge, motivation and professional ethics influence the choice of a career in taxation.Keyword: tax knowledge, motivation and professional ethics, choosing a career in taxation